Application of Dry Probiotic Rabal (Yeast and Lactic Acid Bacteria) to Prevent Mas (Motile Aeromonas Septicemia) Disease in Catfish (Clarias sp.) - Lukman Anugrah Agung; Imas Rohmawati; Eltis Panca Ningsih (Jurnal Biologi Tropis, 2022)
Catfish is one of the important fish commodities in Indonesia. There is some problem that becomes trouble in catfish culture, and the most trouble which cause losses in catfish culture is a disease, especially motile aeromonads septicemia (MAS). The purpose of the study was to analyze the effectiveness of giving dry rabal probiotics for the prevention of motile Aeromonas septicemia (MAS) in catfish (Clarias sp.). This experiment consisted of four treatments, namely catfish farming with the addition of dry rabal probiotics with concentrations of 0%, 5%, 10% and 15%. Catfish (6.03±0.38 g) were reared in a rearing tank with a volume (41x50x57 cm) with a density of 15 fish/aquarium for 50 days. Probiotic bacteria were given daily through feed, while the pathogenic bacteria A. hydrophila was infected on day 51. The results showed that the treatment of giving dry rabal probiotics through feed was effective in improving the immune, and increasing the survival of African catfish. The 10% (C) rabal probiotic treatment gave the best results with the highest survival rate of 75.56 ± 3.85%.